Quark-hadron phase transition in a chameleon Brans-Dicke model of brane gravity - Saaidi, Kh.; Mohammadi, A.; Golanbari, T.; Sheikhahmadi, H.; Ratra, Bharat V. (My University, 2012)
In this work, the quark-hadron phase transition in a chameleon Brans-Dicke model of brane world cosmology within an effective model of QCD is investigated. Whereas, in the chameleon Brans-Dicke model of brane world cosmology, the Friedmann equation and conservation of density energy are modified, resulting in an increased expansion in the early Universe. These have important effects on quark-hadron phase transitions. We investigate the evolution of the physical quantities relevant to quantitative descriptions of the early times, namely, the energy density, p , temperature, T, and the scale factor, a, before, during, and after the phase transition. We do this for smooth crossover formalism in which lattice QCD data is used for obtaining the matter equation of state and first order phase transition formalism. Our analyses show that the quark-hadron phase transition has occurred at approximately one nanosecond after the big bang and the general behavior of temperature is similar in both of two approaches.
Keywords: Quark-hadron phase transition; Brans-Dicke; Brane world cosmology